Invasive plants of the Kampinos National Park outskirts – the current state and threats to the protected area (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Studies aimed at the identification of the range and the ways of spread of invasive alien plants in the Kampinos National Park (KNP) outskirts were carried out between 2012 and mid 2018. Special emphasis was placed on surveying the sites of the invasive species and diagnosing potential threats posed to the natural and semi-natural vegetation of the national park by them in rural areas. A floristic survey was carried out on the majority (93 localities) of settlement areas in the vicinity of KNP, in its buffer zone, frequently near the border of the park. Thirty-nine invasive taxa were found which may potentially pose a threat to the ecosystems of KNP. The most frequently identified species included trees and shrubs: Acer negundo, Rhus typhina, Robinia pseudoacacia, Partenocissuss inserta, and herbaceous plants: Conyza canadensis, Erigeron annuus, Solidago serotinoides, S. canadensis. Species encroaching from the settlement areas to semi-natural and natural communities include Bidens frondosa, Echinocystis lobata, Impatiens glandulifera, I. parviflora, Juncus tenuis, Lupinus polyphyllus, Reynoutria japonica, R. xbohemica and Solidago serotinoides. Most of them are species from the highest (III and IV) classes of invasiveness in Poland. The close distance to the Warsaw conurbation, and the road network developed around KNP has certainly affected the number of alien species recorded in the analysed area. Urbanized lands neighbouring the Park are still probably a source from where alien plants disperse to the protected area.
Keywords: alien flora, biological invasions, invasive species, conservation, central Poland.